PENINGKATAN KINERJA GURU MELALUI KOMPETENSI PROFESIONAL DAN PEDAGOGIK: PERAN MOTIVASI KERJA SEBAGAI MEDIATOR - Dwi Astuti; Ahmad Mukhlis; Angrian Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study explores the influence of professional competence and pedagogical competence on teacher performance and the mediating role of work motivation among private PAUD teachers in Serang District, Serang City, Banten Province. The purpose of this study is to identify the direct and indirect influence of these variables on teacher performance through work motivation. The method used is Structural Equation Modeling - Partial Least Squares (SEM-P2LS) with a quantitative approach, involving 135 respondents from 203 ASN populations. This study provides important insights for improving the performance of private PAUD teachers in Serang District, Serang City, Banten Province by emphasizing the importance of innovative professional competence and improving pedagogical competence based on skills and strengthening teacher work motivation. This strategy can create a more productive work environment.